A pedagogia da participação dos pescadores artesanais na Resex Acaú/Goiana PB, PE: um estudo sobre o orçamento democrático estadual - Pereira, José Adriano de Araújo (2023)
The dissertation study in vogue aims to analyze the process of pedagogy of civil society participation through the territorial dynamics of artisanal fisherwomen and their families included in the Association of Shellfish Makers of Acaú belonging to RESEX Acaú/Goiana in the Paraíba portion and the possible existence of links with the State Democratic Budget in the territory of living. From the 1980s onwards, the issue of participation became more evident with the actions of social movements, becoming a watershed for co-management and strengthened with the 1988 constitution in Brazil. The participation of civil society, through the struggles put in place by social movements, sought to bring movements and their representations closer to the State's decision-making channels after a long process of military dictatorship in Brazil. Among these movements were those of community leaders, traditional peoples, women, LGBTQIAPN+, among others. In the 1990s, there were several participatory experiences of management, co-management, advisors - management councils. The debates held within the scope of the Center for Studies and Research in Social Policies (NEPPS/UFPB) led us to the following problem: what are the political effects related to the pedagogical dimension of the participation policy aimed at artisanal fishing, through the State Democratic Budget at RESEX Acaú/Goiana PB, PE in the Paraíba portion? In the methodological framework we apply the Marxian method based on theoretical concepts from the perspectives of several authors, such as: Ângela Neves, Luciano Avitrizer, Dirce Koga, Milton Santos, Aldaíza Sposati, Emanuel Silva, Marinalva Conserva among others. This work is also the result of field research based on constant dialogue and direct participation, guided tour and use of focus groups with key informants.The combination of methods, also called triangulation, was initially thought of as a strategy to validate results obtained with individual methods, but is currently considered as a way of complementing knowledge and overcoming the potential limitations of the methods used here. This is a qualitative research that made use of participant observation and semi-structured interviews, thus providing a broader relationship between the sender and the receiver within the scope of verbal communication. We characterize the discussion and interpretation of the phenomena studied based on the identification of recurring patterns and a pre-existing theoretical basis. Categorization and systematization were carried out based on Bardin's content analysis. The vocalization of the territory materialized in the subjects gains form, strength, time and voice in the fight for a less authoritarian State; by guaranteeing the decentralization of public resources, aiming to overcome lack of protection at its most varied levels in its territories of existence. The State Democratic Budget (ODE) needs to guarantee the inclusion of social segments in the seats of regional councils and expand ties with the fishing community. Analysis of the results demonstrated that 60% of those interviewed did not know ODE's participation policy; 20% have heard about it, but never participated; 20% claim that they participated in the ODE and claimed that the policy of popular participation in the territory still faces constant conflicts, these arising from political culture in the dispute between the political class and civil society.